The pattern of pegylated interferon-alpha2b and ribavirin treatment failure in cirrhotic patients depends on hepatitis C virus genotype - Aghemo, Alessio; Rumi, Maria Grazia; Monico, Sara; Prati, Gian Maria; D'Ambrosio, Roberta; Donato, Maria Francesca; Colombo, Massimo (Antiviral therapy, 2009)
Failure of anti-hepatitis C therapy encompasses both primary non-response and post-treatment relapse. Treatment failure to pegylated interferon (PEG-IFN)-alpha2b and ribavirin (RBV) largely depends upon virus genotype, but the interaction between genotype, cirrhosis and pattern of treatment failure is unclear. We aimed to assess whether cirrhosis modifies the pattern of PEG-IFN-alpha2b and RBV treatment failure. A total of 471 treatment-naive patients with histologically proven chronic hepatitis C virus (HCV) infection (106 with cirrhosis; 185 with HCV genotype 1 [HCV-1], 157 with HCV genotype 2 [HCV-2], 92 with HCV genotype 3 [HCV-3] and 37 with HCV genotype 4 [HCV-4]) were consecutively treated with PEG-IFN-alpha2b 1.5 microg weekly and weight-based RBV. The sustained virological response (SVR) rates were 31% in HCV-1 and HCV-4, 80% in HCV-2 and 72% in HCV-3, and were lower in cirrhotic than in non-cirrhotic HCV-1 and HCV-4 (17% versus 36%; P=0.01), and HCV-3 (33% versus 79%; P=0.001), but not HCV-2 (69% versus 83%; P=0.1) patients. Treatment failure was the consequence of lower end-of-treatment response rates (37% versus 53%; P=0.06) plus higher post-treatment relapse rates (55% versus 31%; P=0.07) in cirrhotic HCV-1 and HCV-4 patients and higher rates of post-treatment relapse in HCV-2 (29% versus 10%; P=0.01) and HCV-3 cirrhotic patients (61% versus 12%; P<0.001). By multivariate analysis, HCV-1 and HCV-4 (odds ratio [OR] 7.44, 95% confidence interval [CI] 4.87-11.36), and cirrhosis (OR 3.00, 95% CI 1.80-5.00) were independent predictors of treatment failure. Cirrhosis is an important moderator of SVR, accounting for different patterns of treatment failure in patients infected with different genotypes.